2010
DOI: 10.1001/jama.2010.953
|View full text |Cite
|
Sign up to set email alerts
|

Routine Opt-Out Rapid HIV Screening and Detection of HIV Infection in Emergency Department Patients

Abstract: Nontargeted opt-out rapid HIV screening in the ED, vs diagnostic testing, was associated with identification of a modestly increased number of patients with new HIV diagnoses, most of whom were identified late in the course of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
144
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 30 publications
6
144
0
1
Order By: Relevance
“…(23) Our STI screening protocol was designed to mimic the HIV universal screening recommendations by the CDC (ie, screening regardless of sexual activity). (18) Similar to a previous study of HIV screening, (24,25) we found that sexual inexperience and recent testing elsewhere were common reasons for refusal of STI screening. Furthermore, although the reduction of undiagnosed HIV infection through more broad-based screening efforts is a critical public health need, recent data suggests that non-targeted opt-out screening may not significantly increase the number of newly diagnosed HIV infection compared with targeted opt-in HIV screening.…”
Section: Discussionsupporting
confidence: 82%
“…(23) Our STI screening protocol was designed to mimic the HIV universal screening recommendations by the CDC (ie, screening regardless of sexual activity). (18) Similar to a previous study of HIV screening, (24,25) we found that sexual inexperience and recent testing elsewhere were common reasons for refusal of STI screening. Furthermore, although the reduction of undiagnosed HIV infection through more broad-based screening efforts is a critical public health need, recent data suggests that non-targeted opt-out screening may not significantly increase the number of newly diagnosed HIV infection compared with targeted opt-in HIV screening.…”
Section: Discussionsupporting
confidence: 82%
“…41 The implementation of PITC has also led to a high rate of HIV testing among individuals visiting tuberculosis and sexually transmitted infection clinics. 15,[42][43][44] A cluster randomized trial conducted in tuberculosis clinics in South Africa in 2005 found that the introduction of opt-out PITC increased the uptake of HIV testing by 13.7%, from 6.5% when HIV testing was carried out on an opt-in basis to 20.2% with opt-out PITC. 45 The 2011 WHO report on global tuberculosis control stated that HTC is now standard for tuberculosis patients in many countries, especially in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Opt-out testing, electronic reminders, and performance by non-physician staff have been shown to be effective; however, interventions directed at practicing physicians have only increased testing rates to 20-30% of patients seen in these practices, likely due to a combination of provider, patient, and systems barriers. [10][11][12][13] One method to increase levels of guideline adherence by physicians is to encourage adoption during residency training. 14,15 While half of all program directors report that teaching outpatient-based HIV curricula is a priority, 16 it is not known how this training is accomplished or how much emphasis is placed on HIV screening.…”
Section: Introductionmentioning
confidence: 99%